Odpowiedzi

Najlepsza Odpowiedź!
2009-09-07T17:56:02+02:00
A)
3(3x-2)²(x+3)= 3(9x²-12x+4)(x+3)= 3(9x³+27x²-12x²-36x+4x+12)= 27x³+81x²-36x²-108x+12x+36= 27x³+45x²-96x+36
27*(⅔)³+45*(⅔)²-96*⅔+36= 27*8/27+45*4/9-64+36= 8+20-64+36= 0

b)
x(x²+10x+25)(x-1) = (x³+10x²+25x)(x-1) = x⁴-x³+10x³-10x²+25x²-25x = x⁴-9x³+15x²-25x
(-1)⁴+9*(-1)³+15*(-1)²-25*(-1) = 1-9+15+25 = 32

c)
(2-x⁶ - 4x²)(x⁴ - 7x⁶ - 2) = 2x⁴-14x⁶-4-x¹⁰+7x¹²+2x⁶-4x⁶+28x⁸+8x² = 7x¹²-x¹⁰+28x⁸-14x⁶+2x⁶-4x⁶+2x⁴+8x²-4 = 7x¹²-x¹⁰+28x⁸-16x⁶+2x⁴+8x²-4
1 5 1